2017
DOI: 10.1111/1475-6773.12788
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Guideline and Formulary Changes on Statin Prescribing in the Veterans Affairs

Abstract: Addition of a high-potency statin to formulary affected provider prescribing more than the ACC/AHA guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…When it comes to extrapolating the results, one has to bear in mind the fact that the Spanish health system finances practically all me-too drugs at an out-of-hospital level, and this is not necessarily the case elsewhere, e.g. in countries such as the USA or New Zealand [35][36][37].…”
Section: Advantages and Limitationsmentioning
confidence: 99%
“…When it comes to extrapolating the results, one has to bear in mind the fact that the Spanish health system finances practically all me-too drugs at an out-of-hospital level, and this is not necessarily the case elsewhere, e.g. in countries such as the USA or New Zealand [35][36][37].…”
Section: Advantages and Limitationsmentioning
confidence: 99%
“…Despite this, multiple studies have shown that patients’ risk still plays almost no role in current clinical decision-making in CVD prevention [ 1 3 , 14 , 15 , 20 , 21 ]. This is not entirely surprising, since guidelines alone have repeatedly been shown to be inadequate in driving wide-spread implementation of new practices [ 1 , 12 , 20 , 22 ]. Tools to help encourage the use of these guidelines, and to improve cardiovascular prevention in high-risk patients, have had an effect, but only a small one [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 It is estimated that as many as 475 000 future cardiovascular events could be prevented if statins were assigned to all those who exceeded the ≥7.5% cutoff in 10-year ASCVD risk in the 40 to 75 years range. 8 Several reports on statin prescriptions (behavioral change 3,[9][10][11] and total or LDL-cholesterol (physiological responses to the behavioral change 3,4 ) trends proximal to the ACC/AHA guideline release suggest the recommendations have had less impact than anticipated. Although improved LDL-cholesterol levels are no longer the clinical goal following the "treat to ASCVD risk" from the "treat to LDL-cholesterol target" paradigm change, the substantial expansion of the eligible population and shift to moderate-and high-intensity statin therapy should have reduced LDL-cholesterol concentrations nationally.…”
mentioning
confidence: 99%